Clínica Médica e Cirúrgica de Pequenos Animais. - Viana, Ana Carolina Possas (Universidade Federal do Tocantins, 2023)
The traineeshep was conducted at the Veterinary Hospital of the School of Veterinary Medicine and Animal Science of the Federal University of Goias (UFG-HV-EVZ) from November 4th to January 17th, totaling 352 hours. In this period, 127 clinical cases were treated. Trainees were required to follow the monitor residents in attendance, performing anamnesis, physical examination, collection of biological samples, and to monitor surgical procedures, from preoperative until release the patient. This report aims to describe the activities performed at the institution and describe a clinical case accompanied.